THE EPIDEMIOLOGY OF GENITAL TUBERCULOSIS IN REPUBLIC OF BURYATIA DURING 2003-2011 - A. B. Malanova; L. B. Zibikova; O. Y. Leshenko; L. V. Suturina (Acta Biomedica Scientifica, 2012)
We analyzed official statistical data of 2003—2011 concerning incidence and morbidity of genital tuberculosis in Ulan-Ude. We drown a conclusion that the getting data is not reflect the real problems and true data concerning these pathologies has not been studied yet.